Effect of perioperative crystalloid or colloid fluid therapy on hemorrhage, coagulation competence, and outcome: A systematic review and stratified meta-analysis. Issue 31 (August 2016) - Rasmussen, Kirsten C.; Secher, Niels H.; Pedersen, Tom
Abstract : Supplemental Digital Content is available in the text Abstract: Background: A meta-analysis concerning perioperative coagulation competence, hemorrhage, and outcome was conducted including the use of hydroxyethyl starches (HESs), dextran, or albumin versus administration of a crystalloid as control to assess the efficacy and safety of colloids and crystalloids for fluid administration during major elective surgery. Surgery was restricted to cardiovascular and noncardiovascular surgery, and HESs were stratified to HES 130/0.4 and HES 200/0.5. Methods: We searched Cochrane Central Register of Controlled Trials, MEDLINE, ISI Web of Science, EMBASE, conference proceedings, reference lists, and databases of ongoing trials. Results: Thirty one primary clinical randomized controlled trials included 2287 patients undergoing major surgery from January 2000 to August 2015. The perioperative changes in coagulation competence were measured by thromboelastography (TEG) maximum amplitude (MA) in 9 studies administering crystalloids versus HES and in 4 studies administering albumin versus HES. All studies but 1 disclosed increased reduction in TEG-MA following HES administration ( P = 0.0001 and 0.0002). The total loss of blood was reported in 17 studies in which crystalloids were compared to HES and 12 studies reported increased blood loss after administration of HES ( P < 0.003). When administering albumin versus HES, 6 studies reported reduced hemorrhage associated with albumin administration ( P = 0.005). Reoperation was not significantly reduced by the use of crystalloids, but may be more frequent after HESs compared to albumin ( P < 0.03). In this analysis, more patients admitted to administration of HESs were exposed to decrease coagulation competence, compared to perioperative crystalloids and albumin administration. Conclusion: This stratified meta-analysis showed that increased blood loss was found in noncardiovascular surgery among patients receiving HES compared with crystalloids, followed by a marked reduction in TEG-MA, and infusion of 3rd-generation HES products did not influence the results significantly.